2018
DOI: 10.1016/j.vaccine.2018.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Paid sick leave benefits, influenza vaccination, and taking sick days due to influenza-like illness among U.S. workers

Abstract: Introduction: Staying home when sick can reduce the spread of influenza. The objectives of this study were to quantify the percentage of workers who had paid sick leave (PSL) benefits, examine sociodemographic characteristics that may be associated with having these benefits, and examine the association between having PSL benefits and use of sick days and influenza vaccination status. Methods: The public-use dataset from the 2009 National H1N1 Flu Survey (NHFS) were analyzed in 2017. Wald chi-square tests an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 25 publications
1
32
0
1
Order By: Relevance
“…We have documented that workplace cultures that encourage employees to refrain from coming to work when ill may play a crucial role in keeping workers away from the workplace when sick. In this study, persons with access to paid leave worked fewer days overall and at the usual workplace while ill. Two previous studies reported that access to paid sick days was associated with staying home for medically confirmed ILI or influenza ( 23 , 24 ), and 1 study found no association between having paid sick leave benefits and staying home from work because of ILI ( 25 ). These 3 studies did not assess telework.…”
Section: Discussionmentioning
confidence: 99%
“…We have documented that workplace cultures that encourage employees to refrain from coming to work when ill may play a crucial role in keeping workers away from the workplace when sick. In this study, persons with access to paid leave worked fewer days overall and at the usual workplace while ill. Two previous studies reported that access to paid sick days was associated with staying home for medically confirmed ILI or influenza ( 23 , 24 ), and 1 study found no association between having paid sick leave benefits and staying home from work because of ILI ( 25 ). These 3 studies did not assess telework.…”
Section: Discussionmentioning
confidence: 99%
“…We found limited evidence that workplace measures and closures would be effective in reducing influenza transmission. Two recent studies not included in our systematic review have contrasting findings on the effect of having paid sick leave and taking a day off from work because of ILI (46,47). As with school closures, the timing and duration of workplace interventions would be a critical issue affecting their impact in mitigating a pandemic.…”
Section: Workplace Measures and Closuresmentioning
confidence: 98%
“…The associations of ILI and workplace absenteeism with occupation and other demographic characteristics are complex and mediated by factors such as vaccination coverage and access to paid sick leave ( 9 ). More study using additional data sources is needed to fully understand the reasons for increases in absenteeism related to sex, age, or specific occupations that are identified by these surveillance analyses.…”
Section: Discussionmentioning
confidence: 99%